“Tulun IYA”. The concept of improvement of Lenin Street - Falkovsky, Dmitry; Tkacheva, Marina (project baikal, 2021)
The article reviews historical, natural, landscape and economic conditions for the development of Tulun. The authors propose strategies of renovation of the city center, including economy restructuring, usage of urban mentality and existing urban activities, as well as citizen participation in design and territory management.
Keywords: Tulun; Iya; strategies of urban transformation; design; economy; advancement; organization